Body Modification as Body Art: Aging, Abjection, and Autothanatology - Cameron, Jessica (Atlantis, 2024)
In this article, I discuss my “anti-aging” body modification practices as body art. The art documents my bodybuilding programs, self-administered neurotoxin (Botox) injections, and skin resurfacing treatments. Susan Pickard (2020) argues that femininity and aging are associated with the abject. She maps the abject and non-abject onto Simone de Beauvoir’s distinction between immanence and transcendence. Because “abjection should always be understood as an element of [...] oppression” (Pickard 2020, 159), my art practice could be read as an anti-feminist, ageist attempt to expel the abject. After offering a counter-argument that positions my practice as feminist, I use Kathy Acker’s (1993) writing on bodybuilding to offer a third reading. Muscles grow when they are worked until failure. This practice of constantly coming up against the body’s limits is a rehearsal for the ultimate failure of the body: death (Acker 1993). If thanatology is the study of death and dying, bodybuilding is autothanatology. My “anti-aging” interventions are similar; they are inevitable failures that cannot stop the aging process. In this way, my practice is a reminder that the body exists in a state of immanence, even while I may attempt to frame my immanence along transcendental terms.